1993
DOI: 10.1016/0014-5793(93)81716-d
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of thrombin require sustained activation of the functional thrombin receptor

Abstract: Thrombin is a potent activator of human glomerular epithelial cells (HGEC). Here we compare short-term and long-term effects of thrombin and thrombin receptor agonist peptide (TRAP) which selectively activates the functional thrombin receptor. TRAP, as thrombin, increases intracellular free Ca 2÷ concentration and acts synergistically with growth factors possessing tyrosine kinase receptors on DNA synthesis. Thrombin induces synthesis of proteins of the fibrinolytic system and cell proliferation if it is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Whether peptide degradation is mediated by proteases secreted into the medium, or via receptormediated endocytosis, as for EGF via its receptor, remains to be determined. Our results using amastatin were entirely in accord with the study of Zacharias and co-workers, who found that amastatin was required to observe a mitogenic action of the TRAP, SFLLRNP in cultured human glomerular epithelial cells (Zacharias et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…Whether peptide degradation is mediated by proteases secreted into the medium, or via receptormediated endocytosis, as for EGF via its receptor, remains to be determined. Our results using amastatin were entirely in accord with the study of Zacharias and co-workers, who found that amastatin was required to observe a mitogenic action of the TRAP, SFLLRNP in cultured human glomerular epithelial cells (Zacharias et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…As shown in Fig. 6, fibroblasts express a 3.4-kb thrombin receptor transcript, in agreement with an earlier report (21). Our analysis indicated that keratinocytes contain comparable levels of the thrombin receptor transcript.…”
supporting
confidence: 80%
“…1 C and D). Thrombin and SFLLRN induced inositol phosphate formation and calcium mobilization to similar extents, although the doses of SFLLRN required for receptor activation were greater than those for thrombin, as observed in other cell systems (4,20,21 1 and Fig. 2).…”
mentioning
confidence: 88%
“…However, it is now evident that the transient nature of the responses to TRPs are due in some cases to the metabolism of the peptides by cellular aminopeptidase M, an enzyme present in plasma, leucocytes, smooth muscle, vascular endothelium and other cell types, which removes the terminal Ser to inactivate the TRPs, but which apparently does not attack the N-terminal Ser of the TL in the large native receptor molecule (Coller et al, 1992). Amastatin, a very potent inhibitor of the peptidase, potentiated aggregation of platelets in plasma by TRPs (Coller et al, 1992) and enabled a long-term mitogenic activity of TRPs in kidney epithelial cells (Zacharias et al, 1993). However, the differences between TRPs and thrombin in our experiments on washed human platelets were clearly not attributable to the metabolic destruction of the TRPs, because the incubation of TRPs with stimulated platelets and their secretory products did not diminish their agonist activity, and responses to TRPs were not potentiated or prolonged by amastatin.…”
Section: Discussionmentioning
confidence: 99%